Is the modified shuttle test a maximal effort test in children and adolescents with asthma?. Issue 1 (12th October 2021) - Reimberg, Mariana M.; Ritti‐Dias, Raphael; Selman, Jessyca P.; Scalco, Rebeca S.; Wandalsen, Gustavo F.; Solé, Dirceu; Hulzebos, Erik J.; Takken, Tim; Dal Corso, Simone; Lanza, Fernanda C.
Abstract: Purpose: Whether the modified shuttle test (MST) achieves maximal effort in children and adolescents with asthma is unclear. The aim was to compare the physiological responses of MST to the cardiopulmonary exercise test (CPET) in pediatric patients with asthma, to observe its convergent validity. Patients and Methods: A cross‐sectional study with volunteers with asthma (6–17 years of age) under regular treatment. The MST is an external‐paced test, and the participants were allowed to walk/run. CPET was performed on a cycle ergometer to compare with MST. Gas exchange (VO2, VCO2, and VE) and heart rate (HR) were the outcomes and were continuously assessed in both tests. Results: Forty‐seven volunteers were included, normal lung function expiratory forced volume at 1st second/forced vital capacity (FEV1 /FVC) 88.6 (7.7). VO2peak was higher at MST (2.0 ± 0.6 L/min) compared to CPET (1.6 ± 0.5 L/min), p < 0.001. Similar results was observed to VE at MST (50 ± 16 L/min) versus VE at CPET (40 ± 13 L/min), and to VCO2 at MST (2.1 ± 0.8 L/min) versus VCO2 at CPET (1.7 ± 0.6 L/min), p < 0.001. HR was also higher at MST (94 ± 6%pred) versus CPET (87 ± 8%pred), p = 0.002. VO2peak in MST correlated to the CPET ( r = 0.78, p < 0.001). The ICC of VO2peak between tests was 0.73 (0.06–0.89), p < 0.001, and VO2peak Bland–Altman analysis showed a bias of 0.46 L/min. Conclusion: The MST showed a maximal physiologic response in children and adolescents with asthma. It is a valid test and can be used as an alternative to evaluating exercise capacity.